Are the European Commission's forecasts of public finances better than those of national governments? - Jakub Rybacki (Central European Economic Journal (CEEJ), 2020)
The academic literature in the past has frequently highlighted that the European Commission (EC) tends to provide more accurate public finance forecasts compared with national governments, thanks to its neutrality. The recent conflicts regarding the excessive deficit procedure with Romania and Italy and rule of law with Hungary and Poland raises the question of whether such conclusions are still binding. Therefore, we analysed a panel of forecasts submitted by the national governments with an annual update of Convergence programmes and corresponding EC predictions. Our dataset contains predictions of the general government deficit, revenues and expenditures for EU27 economies and the United Kingdom in the years 2014-2019. First, the analysis shows no meaningful discrepancies between both estimates when the horizon is set at the current year. Forecasts for the next year have equal accuracy in the case of government revenues and expenditures. However, the EC performs worse in the case of the final deficit. Second, cross-country effects are present, but the accuracy is different mainly in the very small economies, that is, the Baltic countries, Cyprus, Malta and Luxembourg. Amongst the more populated states, the EC outperforms the Slovakian and Denmark governments but has worse performance than the Irish, Portuguese and Spanish governments. We also do not see evidence of any political bias in the forecasts.
Keywords: H62; H68; 330; fiscal forecasts; convergence programme